2012
DOI: 10.1200/jco.2011.37.8018
|View full text |Cite
|
Sign up to set email alerts
|

Improved Survival for Children and Adolescents With Acute Lymphoblastic Leukemia Between 1990 and 2005: A Report From the Children's Oncology Group

Abstract: A B S T R A C T PurposeTo examine population-based improvements in survival and the impact of clinical covariates on outcome among children and adolescents with acute lymphoblastic leukemia (ALL) enrolled onto Children's Oncology Group (COG) clinical trials between 1990 and 2005. Patients and MethodsIn total, 21,626 persons age 0 to 22 years were enrolled onto COG ALL clinical trials from 1990 to 2005, representing 55.8% of ALL cases estimated to occur among US persons younger than age 20 years during this per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
807
7
27

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 1,007 publications
(866 citation statements)
references
References 46 publications
25
807
7
27
Order By: Relevance
“…The acute lymphoblastic leukemia (ALL) is the malignant tumor with the highest incidence in the childhood, although the risk-stratification chemotherapy has significantly improved the prognosis, the event-free survival (EFS) and overall survival (OS) have been significantly improved, the recurrence and disease progression, as well as the drug toxicity -related mortality, are still increasing (Hunger et al, 2012). The recent studies have found that during the child critical disease process, the incidence of hyperglycemia was one of the risk factors that would affect the prognosis (Devos and Preiser, 2004;Faustino and Apkon, 2005), and the similar conclusion had been confirmed in the adult malignancies (Ali et al, 2007), the hyperglycemia might directly affect the cell growth, and induce the drug resistance of tumor cells (Feng et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The acute lymphoblastic leukemia (ALL) is the malignant tumor with the highest incidence in the childhood, although the risk-stratification chemotherapy has significantly improved the prognosis, the event-free survival (EFS) and overall survival (OS) have been significantly improved, the recurrence and disease progression, as well as the drug toxicity -related mortality, are still increasing (Hunger et al, 2012). The recent studies have found that during the child critical disease process, the incidence of hyperglycemia was one of the risk factors that would affect the prognosis (Devos and Preiser, 2004;Faustino and Apkon, 2005), and the similar conclusion had been confirmed in the adult malignancies (Ali et al, 2007), the hyperglycemia might directly affect the cell growth, and induce the drug resistance of tumor cells (Feng et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although prior to 1950, the diagnosis of childhood leukemia was uniformly fatal and in the 1960s survival was only 15-20%, survival rates for childhood ALL have now reached 90% (26). Figure 2 shows the dramatic decline in mortality rates for ALL and other pediatric cancers.…”
Section: Curing a Common Childhood Cancermentioning
confidence: 99%
“…After developing special tools to measure surface Gestational age (weeks) 26 Special Article tension, he identified pulmonary surfactant (first called the "anti-atelectasis factor") (40). Avery and Mead made the seminal discovery that surfactant was absent from the lungs of infants who died from RDS, but present in infants who died without pulmonary disease (41).…”
Section: Saving Premature Babiesmentioning
confidence: 99%
“…Boys, irrespective of risk of testicular relapse, have a slightly inferior outcomes compared with girls. 26 Black and Hispanic children with ALL have been shown to have an inferior outcome compared with Caucasian and Asian children. 27 The reasons underlying these disparities are likely multiple, but include variations in ALL subtypes, host polymorphisms, and sociodemographic factors.…”
Section: Clinical Featuresmentioning
confidence: 99%